Distribution of Tetrahydromethanopterin-Dependent Enzymes in Methylotrophic Bacteria and Phylogeny of Methenyl Tetrahydromethanopterin Cyclohydrolases - Vorholt, Julia A. (American Society for Microbiology, 1999)
The methylotrophic proteobacterium Methylobacterium extorquens AM1 possesses tetrahydromethanopterin (H(4)MPT)-dependent enzymes, which are otherwise specific to methanogenic and sulfate-reducing archaea and which have been suggested to be involved in formaldehyde oxidation to CO(2) in M. extorquens AM1. The distribution of H(4)MPT-dependent enzyme activities in cell extracts of methylotrophic bacteria from 13 different genera are reported. H(4)MPT-dependent activities were detected in all of the methylotrophic and methanotrophic proteobacteria tested that assimilate formaldehyde by the serine or ribulose monophosphate pathway. H(4)MPT-dependent activities were also found in autotrophic Xanthobacter strains. However, no H(4)MPT-dependent enzyme activities could be detected in other autotrophic α-proteobacteria or in gram-positive methylotrophic bacteria. Genes encoding methenyl H(4)MPT cyclohydrolase (mch genes) were cloned and sequenced from several proteobacteria. Bacterial and archaeal Mch sequences have roughly 35% amino acid identity and form distinct groups in phylogenetic analysis.